Computations of uncertainty mediate acute stress responses in humans - de Berker, Archy O.; Rutledge, Robb B.; Mathys, Christoph; Marshall, Louise; Cross, Gemma F.; Dolan, Raymond J.; Bestmann, Sven (Nature communications, 2016)
The effects of stress are frequently studied, yet its proximal causes remain unclear. Here we demonstrate that subjective estimates of uncertainty predict the dynamics of subjective and physiological stress responses. Subjects learned a probabilistic mapping between visual stimuli and electric shocks. Salivary cortisol confirmed that our stressor elicited changes in endocrine activity. Using a hierarchical Bayesian learning model, we quantified the relationship between the different forms of subjective task uncertainty and acute stress responses. Subjective stress, pupil diameter and skin conductance all tracked the evolution of irreducible uncertainty. We observed a coupling between emotional and somatic state, with subjective and physiological tuning to uncertainty tightly correlated. Furthermore, the uncertainty tuning of subjective and physiological stress predicted individual task performance, consistent with an adaptive role for stress in learning under uncertain threat. Our finding that stress responses are tuned to environmental uncertainty provides new insight into their generation and likely adaptive function. Acute stress has broad physiological and behavioural consequences, yet the precise factors that generate stress responses are not known. Here, de Berker and colleagues demonstrate that acute stress responses dynamically track environmental uncertainty and predict ability to learn under uncertain threat.